2018
DOI: 10.1080/1028415x.2017.1423268
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A and vitamin D deficiencies exacerbate symptoms in children with autism spectrum disorders

Abstract: We found that children with autism have more VA and VD deficiencies than control children, and VA and VD co-deficiency may exacerbate the symptoms of children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 42 publications
8
28
0
1
Order By: Relevance
“…The results showed that in children with AD, serum VD levels were negatively correlated with the severity of the disease ( r = –0.3880, p = 0.0004), consistent with the results of previous studies [19, 22, 23] (Fig. 2a).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The results showed that in children with AD, serum VD levels were negatively correlated with the severity of the disease ( r = –0.3880, p = 0.0004), consistent with the results of previous studies [19, 22, 23] (Fig. 2a).…”
Section: Resultssupporting
confidence: 82%
“…Oh et al [20] reported that the incidence of AD was negatively correlated with the intake of antioxidant nutrients (including retinol and β-carotene), and Mihály et al [21] found decreased retinoid concentration and retinoid signalling pathways in human AD patients. Our previous studies demonstrated that VA and VD co-deficiency may exacerbate the symptoms of children with autism spectrum disorders [22]. No studies have reported the serum levels of VA in children with AD or explored whether there is a synergistic effect between VD and VA in AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin A de ciency (VAD) is still a public health issue in many developing countries. Studies showed ASD children are more vulnerable to VAD than neurotypical children [19] [20]. In our study, an increased level of 4'-apo-beta-carotenal, b,e-carotene-3,3'-diol and decreased retinol may indicate that ASD children had decreased capacity of absorption and bioconversion of plant-origin precursors of vitamin A. Vitamin A has three active forms, retinal, retinol and retinoic acid (RA) in humans [21].…”
Section: Discussionmentioning
confidence: 56%
“…Otizm hastalarında Guo ve ark. 27 A vitamin düzeyinin, Bakkaloğlu ve ark. 28 A, C ve E vitamin düzeylerinin, Al-Gadani ve ark.…”
Section: Gereç Ve Yöntemunclassified